COMMUNITY PERCEPTION ON THE PERFORMANCE OF THE REGIONAL PEOPLE'S REPRESENTATIVE BOARD OF NABIRE REGENCY IN 2019-2020 - Simon Tiranda; Caroline Paskarina; Rahman Mulyawan (DIA: Jurnal Administrasi Publik, 2023)
The phenomenon in the field shows that there is public dissatisfaction with the performance of the Regional People's Representative Council of Nabire Regency which is considered not optimal. This is because the implementation of village infrastructure development such as roads, there are still many violations and irregularities. Violations that occur in infrastructure development are the construction of roads that are not up to standard, so that there are still many roads in the Nabire district that are easily damaged. This research uses quantitative methods. The population of this study was limited to the adult population of Nabire Regency. This is intended to facilitate researchers in conducting sampling that requires a sample frame. Researchers used the Permanent Voters List for the 2019 general election based on data from the Nabire Regency Regional General Election Commission. The results showed that the Nabire Regency Regional House of Representatives carried out four functions, namely the functions of legislation, supervision, budgeting and harmonization with the local government. The supervisory function is carried out best inversely with the harmonization function with the local government. There seems to be a tendency that if the supervisory function is carried out better it will have an impact on the tendency of harmonization with local governments to decline.